2015
DOI: 10.1016/j.freeradbiomed.2015.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum antioxidant protein reveals a novel mechanism for balancing turnover and inactivation of peroxiredoxins

Abstract: Life under aerobic conditions has shaped peroxiredoxins (Prx) as ubiquitous thiol-dependent hydroperoxidases and redox sensors. Structural features that balance the catalytically active or inactive redox states of Prx, and, therefore, their hydroperoxidase or sensor function, have so far been analyzed predominantly for Prx1-type enzymes. Here we identify and characterize two modulatory residues of the Prx5-type model enzyme PfAOP from the malaria parasite Plasmodium falciparum. Gain- and loss-of-function mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(61 citation statements)
references
References 63 publications
5
56
0
Order By: Relevance
“…2a). The detected consumption of NADPH in the presence of artemisinins or di- tert -butyl peroxide (DTBP) was comparable to the background activity of negative controls without peroxide substrate, whereas the conversion of tert -butyl hydroperoxide (tBOOH) served as a positive control as described previously 45, 47 . Thus, Pf AOP does not convert endoperoxides and its enzymatic activity is restricted to hydroperoxide substrates.
Figure 2Peroxidase activity of recombinant Pf AOP in the presence of artemisinins.
…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…2a). The detected consumption of NADPH in the presence of artemisinins or di- tert -butyl peroxide (DTBP) was comparable to the background activity of negative controls without peroxide substrate, whereas the conversion of tert -butyl hydroperoxide (tBOOH) served as a positive control as described previously 45, 47 . Thus, Pf AOP does not convert endoperoxides and its enzymatic activity is restricted to hydroperoxide substrates.
Figure 2Peroxidase activity of recombinant Pf AOP in the presence of artemisinins.
…”
Section: Resultsmentioning
confidence: 67%
“…2c). No inhibitory effects were detected except for the positive control with tBOOH, which is not only a substrate but also an irreversible inhibitor that ‘overoxidizes’ Pf AOP 45, 47 . In summary, artemisinins are neither reversible nor irreversible inhibitors of recombinant Pf AOP and enzymatic assays do not support a direct effect of Pf AOP on artemisinins and vice versa .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In our roGFP2 assays we choose to use H 2 O 2 to initiate GSSG formation. Whilst yeast do not harbor any bona fide glutathione peroxidase, it was recently shown that GSH and/or Grx can reduce both 1-Cys and typical 2-Cys peroxiredoxins thereby leading to GSSG production 42,46,47,49,50 . Furthermore, GSSG was shown to readily accumulate in Δglr1 cells following H 2 O 2 treatment 45 .…”
Section: Discussionmentioning
confidence: 99%